Analysis of the biodiversity of vertebrate fauna on a farm in Caldas, Antioquia - Quintana Diosa, Lizeth E. (Universidad de La Salle. Revistas. Revista de Medicina Veterinaria., 2016)
Objective: The study analyzed the composition of the vertebrate fauna community in a very humid premontane forest area in the Santa Inés practice center, located in the municipality of Caldas (Antioquia, Colombia), with an area of 124,085 m2, of limey-clayish and limey-sandy soil, at an altitude between 1800-2000 meters a.s.l., and with an average rainfall of 2444 mm. Materials and methods: As a non-invasive technique, camera traps were used during a sampling period of fifteen weeks, with seven cameras, rotating them every three weeks, and using baits to facilitate observation. A final rotation was performed to determine relative abundance, which lasted three months. Results: During the entire sampling period, 23 species were recorded: 11 from the Mammalia class and 12 from the bird class; with a total effort of 1099 days/trap. The photos obtained in each sampling station allowed to analyze the relationship among the species found; five species of wild cats were also recorded. The 13.043 % of all recorded species are in a risk category according to international standards. Conclusions: As the basis of this study, there was observed, for the first time, the macrovertebrate wildlife living in the forest area of the Santa Inés practice center, where various mammals and birds were recorded; this shows the effectiveness of camera traps. The pattern of activity of the recorded species determined diurnal and nocturnal habits.